METAMORPHIC DIAMONDS: MECHANISM OF GROWTH AND INCLUSION OF OXIDES - Dobrzhinetskaya L.F.; Green II H.W.; Mitchell T.E.; Dickerson R.M. (My University, 2001)
We report a detailed series of electron microscope observations of metamorphic microdiamonds included in and separated from garnets and zircons from a single specimen of garnet-biotite-feldspar gneiss from the Kokchetav massif, Kazakhstan. The morphology of the diamonds ranges from skeletal forms composed of thin {111} plates through cuboid and octahedral forms. Included within the diamonds is a diverse suite of nanometric oxides, suggesting that the C-O-H fluid from which the diamonds grew may have carried chemical components derived from both the sediments and the mantle. The spectrum of morphologies and their abundant tiny inclusions can all be explained by a simple model based on the ratio of the rate at which {111} plates grow and the rate of random nucleation of new plates at their edges.
Keywords: diamonds; inclusions; oxides; eskolaite; magnesite; mechanism; crystal growth